The Influence of Inquiry-Based Learning Model on Scientific Literacy in the Rotational Dynamics of a Rigid Bodies - Dewa Gede Eka Setiawan; Asri Arbie; Anisa Fauzia; Trisnawaty Junus Buhungo; Supartin Supartin; Citron S. Payu; Muhammad Yunus (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the influence of the Inquiry-Based Learning model on students' scientific ability in Rotational Dynamics of a Rigid Bodies. This influence is seen from whether or not students can achieve the criteria of completeness by mastering three PISA (Program for International Student Assessment) indicators in 10 items on the test consisting of two questions to identify scientific problems, five question to explain phenomena scientifically, and three questions to interpret data and scientific evidence. The research method applied is the experimental method and uses the One Group Pretest-Posttest Design as a research design involving 4 classes, where 1 class acts as the experimental class and 3 classes as the replication class. Based on the statistical results of the t-test to test the research hypothesis, the t-count value for each sample class is greater than the t-table value. This shows that the use of the Inquiry-Based Learning learning model has an effect on students' scientific literacy abilities in the rotational dynamics of a rigid bodies